PEMBUATAN MEDIA PEMBELAJARAN BERBASIS COMPUTATIONAL THINKING (CT) BAGI GURU PAUD - Takumansang, Regina Christine; Wati, Sindy Anugerah; Anggraini, Kristin; Simanjuntak, Anita Roslina (LPPM Universitas Bina Bangsa, 2025)
This activity is designed to improve teachers' understanding of CT concepts and principles, as well as practical skills in designing interactive and engaging CT-based learning media. The training lasted for five days, divided into two stages, where participants were taught about CT components, such as decomposition, pattern recognition, abstraction, and algorithms, and how to integrate them into learning according to the child's developmental stage. Through this community service, teachers had the opportunity to share experiences and ideas and provide constructive feedback to each other. This community service shows that the training has succeeded in improving the knowledge and skills of Avicenna Kindergarten teachers in creating Computational Thinking (CT)-based learning media. In addition, the media produced is expected to help children develop problem-solving skills, critical, creative, and analytical thinking from an early age. Thus, this activity is a significant initial step to improve the quality of education at Avicenna Kindergarten Surabaya and prepare children to face challenges in the digital era.